2021
DOI: 10.3390/healthcare9040373
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Alcohol Hangover on Response Inhibition and Attentional Bias towards Alcohol-Related Stimuli

Abstract: Alcohol hangover is associated with the development of alcohol use disorders, yet few studies have examined the influence of hangover on cognitive processes that may contribute towards future alcohol consumption such as response inhibition and attentional bias towards alcohol-related stimuli. Therefore, the current study aimed to explore the effects of hangover on these processes. In total, 37 adult drinkers who reported regularly engaging in heavy episodic drinking and experiencing a hangover at least once in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…Goal maintenance is thought to represent the 'common factor' of the unity/diversity model, and an important aspect of maintaining goals is inhibitory control [15]. Therefore, impaired goal maintenance during a hangover may contribute toward findings of previous studies of executive functions that have reported impaired prospective memory, semantic verbal fluency [10], working memory, [12], and inhibitory control [5,6,30] during a hangover relative to a no-hangover condition. Contrary to our hypothesis, there was no evidence that participants were biased toward reactive control during a hangover, suggesting participants engaged in proactive control during this task, but were ineffective in doing so (as evidenced by increased errors on the core AX-type trials).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Goal maintenance is thought to represent the 'common factor' of the unity/diversity model, and an important aspect of maintaining goals is inhibitory control [15]. Therefore, impaired goal maintenance during a hangover may contribute toward findings of previous studies of executive functions that have reported impaired prospective memory, semantic verbal fluency [10], working memory, [12], and inhibitory control [5,6,30] during a hangover relative to a no-hangover condition. Contrary to our hypothesis, there was no evidence that participants were biased toward reactive control during a hangover, suggesting participants engaged in proactive control during this task, but were ineffective in doing so (as evidenced by increased errors on the core AX-type trials).…”
Section: Discussionmentioning
confidence: 96%
“…Recent studies have indicated that executive functions may be negatively influenced by alcohol hangovers. Studies have suggested that performance on tasks of interference control [4,5] and response inhibition [6] is impaired when subjects are experiencing a hangover, suggesting poorer inhibitory control, which may negatively influence decisions around subsequent alcohol use [7] and emotion regulation [8]. Furthermore, findings showing poorer spatial working memory [4], reward learning [9], prospective memory [10,11], semantic verbal fluency [10], and performance on backward visual span tasks [12] indicate that executive functions are impaired whilst experiencing a hangover.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, although AH severity positively correlated with three factors on the NASA-TLX, there was no other evidence of a relationship between AH severity, mental workload, and task performance. Recent research has been mixed regarding the relationship between AH severity and performance, with some studies reporting select associations (Alford et al 2020a ; Ayre et al 2021 ) and others not (Gunn et al 2020 , 2021 ). We previously found correlations between total AH severity and the severity of individual symptoms (e.g., fatigue) with times to complete the trail-making task B (a measure of psychomotor speed and cognitive flexibility).…”
Section: Discussionmentioning
confidence: 99%
“…In relation to attentional processes, several studies have reported impairments in sustained (Howland et al 2010 ; McKinney et al 2012 ; Rohsenow et al 2010 ) and selective attention (Devenney et al 2019 ; McKinney et al 2012 ), as well as reduced self-reported alertness (Benson et al 2020 ; Devenney et al 2019 ; McKinney and Coyle 2007 ; Verster et al 2003 ) and concentration (Finnigan et al 2005 ; Slutske et al 2003 ; Verster et al 2014 ). Along with higher ratings of perceived mental effort and demand (Gunn et al 2020 , 2021 ), this suggests an association with reduced attentional resources during AH.…”
Section: Introductionmentioning
confidence: 92%